The Catalyst behind Sri Lanka Downfall: Overdependence and the Failure of Protectionism - Alamari, Muhammad Fauzan (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2022)
Sri Lanka shocked the world with a downfall due to an economic crisis. Among the states that had to mitigate the pandemic, Sri Lanka appears to struggle with the situation and as a result of this event, Sri Lanka is in a position of overdue debt with a total of 51 billion USD worth of debt. The inflation was created by economic shortage activity with imbalanced trade records leads to the overthrown of Sri Lanka’s president and as the result produced a vacuum of power. This paper will use of dependency theory to describe the cause of Sri Lanka’s collapse by examining several factors such as civil war, pandemic, oil price rise, and recent terrorist attack.